The indispensable contribution of s38 protein to ovarian-eggshell morphogenesis in Drosophila melanogaster. Issue 1 (December 2018) - Velentzas, Athanassios; Velentzas, Panagiotis; Katarachia, Stamatia; Anagnostopoulos, Athanasios; Sagioglou, Niki; Thanou, Eleni; Tsioka, Maria; Mpakou, Vassiliki; Kollia, Zoe; Gavriil, Vassilios; Papassideri, Issidora; Tsangaris, George; et al.
Abstract Drosophila chorion represents a remarkable model system for thein vivo study of complex extracellular-matrix architectures. For its organization and structure, s38 protein is considered as a component of major importance, since it is synthesized and secreted during early choriogenesis. However, there is no evidence that proves its essential, or redundant, role in chorion biogenesis. Hence, we show that targeted downregulation of s38 protein, specifically in the ovarian follicle-cell compartment, via employment of an RNAi-mediated strategy, causes generation of diverse dysmorphic phenotypes, regarding eggshell's regionally and radially specialized structures. Downregulation of s38 protein severely impairs fly's fertility and is unable to be compensated by the s36 homologous family member, thus unveiling s38 protein's essential contribution to chorion's assembly and function. Altogether, s38 acts as a key skeletal protein being critically implicated in the patterning establishment of a highly structured tripartite endochorion. Furthermore, it seems that s38 loss may sensitize choriogenesis to stochastic variation in its coordination and timing.